PEMBERDAYAAN KADER POSYANDU MELALUI PELATIHAN DAN SKRINING KESEHATAN BERBASIS PENDEKATAN PROMOTIF PREVENTIF UNTUK PENCEGAHAN DIABETES MELITUS DI DESA CILEMBER - Friska; Adelia Sandra Dwi; Salsabila; Siti Jesi Ira; Delia Ratnasari; Resti Anjani; Deni Saputra; Muhamad Ramadhan (P3M Universitas Aisyiyah Surakarta, 2026)
ABSTRACT DM is a non-communicable disease that disrupts the body's metabolic functions and contributes to various complications. People with DM are often unaware of the early symptoms of diabetes. Many cases of diabetes mellitus are also found to be caused by excessive weight gain or obesity. It is estimated that there will be 783 million cases of diabetes by 2045. To conduct training and mentoring for health cadres in measuring blood sugar and strengthening health promotion strategies among residents as an effort to control non-communicable diseases, especially diabetes mellitus, in Cilember Village. This community service activity was carried out through an initial survey, education about diabetes and obesity, blood sugar level checks, training in the use of glucometers, and the donation of glucometers, as well as an evaluation of the activity. The cadres were enthusiastic and confident in checking the blood sugar levels of the community in Cilember Village. The results of the examination showed that there were 20 residents at high risk of diabetes out of 35 residents who underwent screening. The role of the integrated health service post and the cadres themselves in reducing the incidence of non-communicable diseases, particularly diabetes mellitus and obesity among the community, needs to be improved and optimised.